A cross-sectional study on the quality of care provided by lower health facilities in Kyegegwa district, Uganda. - Mushabe, Robert; Kazibwe, Francis; Laban, Waswa Bright (Student's Journal of Health Research Africa, 2025)
Maternal and neonatal health remains a pressing global concern, particularly in low-resource settings such as Kyegegwa District, Uganda. Despite ongoing improvements in healthcare infrastructure, gaps in service delivery at lower health facilities contribute to persistently high maternal and neonatal morbidity and mortality. This study aimed to assess the quality of maternal and neonatal care provided by lower health facilities in Kyegegwa District. Methods A cross-sectional study was conducted among 80 respondents, including mothers attending antenatal, delivery, and postnatal services. Data were collected using structured questionnaires and analyzed using descriptive statistics, bivariate, and multivariate analyses to determine associations between quality of care and influencing factors. Results Of the participants, 62.5% were aged between 20–29 years, 70% were married, and 55% had attained primary education as their highest level. Overall, only 25% of respondents rated the quality of maternal and neonatal care as excellent, 45% rated it as fair, and 30% rated it as poor. High-quality maternal and neonatal care was significantly associated with regular health facility visits (χ²=12.46, p<0.001). Other factors included the availability of skilled and friendly healthcare workers (78%), presence of essential medicines (65%), availability of proper equipment (52%), effective communication (60%), and timely coordination with referral hospitals (48%). However, challenges such as understaffing, drug stock-outs, and limited infrastructure undermined service delivery. Conclusion The quality of maternal and neonatal care in lower health facilities in Kyegegwa District is suboptimal, with the majority of mothers rating services as fair or poor. Regular health facility visits and the presence of skilled, well-equipped, and patient-centered healthcare workers were key determinants of high-quality care. Recommendation Government should strengthen maternal and neonatal healthcare by recruiting and retaining skilled health workers, improving drug and equipment supply, and enhancing referral systems. Additionally, healthcare workers should adopt a respectful, patient-centered approach to improve mothers’ experiences and outcomes.